2024
DOI: 10.2147/prbm.s440958
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Perceived Discrimination on Mobile Phone Addiction Among Chinese Higher Vocational College Students: A Chain Mediating Role of Negative Emotions and Learning Burnout

Wenping Li,
Ting Xu,
Liuting Diao
et al.

Abstract: Perceived discrimination among higher vocational college students is a prevalent issue in China and is linked to various mental and behavioral problems, including mobile phone addiction. Yet, the mechanisms underlying the relationship between perceived discrimination and mobile phone addiction remain ambiguous. Methods: To address this issue, we recruited 1253 higher vocational college students to elucidate the relationship between perceived discrimination and mobile phone addiction. Participants completed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Mobile phone addiction refers to the excessive use of and dependence on mobile phones that leads to problematic psychology or behavior in daily life, known as mobile phone dependence, mobile phone problematic use, and mobile phone addiction [ 2 ]. Previous studies have shown that mobile phone addiction can negatively affect college students’ academic performance, mental health, physical health, and social functioning, such as reducing academic engagement [ 3 , 4 ]. inducing depression [ 5 – 7 ],and procrastination [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phone addiction refers to the excessive use of and dependence on mobile phones that leads to problematic psychology or behavior in daily life, known as mobile phone dependence, mobile phone problematic use, and mobile phone addiction [ 2 ]. Previous studies have shown that mobile phone addiction can negatively affect college students’ academic performance, mental health, physical health, and social functioning, such as reducing academic engagement [ 3 , 4 ]. inducing depression [ 5 – 7 ],and procrastination [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%